Interkulturelles Lernen durch Theater. Theoretische Perspektiven und praktische Beispiele für den Literaturunterricht der Sekundarstufe - Paumgardhen, Paola (Kritik. Rivista di letteratura e critica culturale, 2023)
This article focuses firstly on theoretical aspects of intercultural learning through theatre in secondary school in Italy and presents various theatrical teaching approaches. Secondly, it proposes a lesson plan based on the concept of literary learning developed by several educational experts, in particular by Kaspar H. Spinner. The lesson aims at developing intercultural competence through Gotthold Ephraim Lessing’s drama Die Juden.